Ridge dimensional changes following single‐tooth extraction in the aesthetic zone - Farmer, Mark; Darby, Ivan (Clinical oral implants research, 2014)
Objectives The aims of this study were to investigate the magnitude of the dimensional changes following extraction of a single tooth in the aesthetic zone over a 6‐ to 8‐week healing period and to examine the degree and pattern of resorption of the buccal bone plate during this time frame. Materials and methods Twenty subjects who were to have a single tooth in the aesthetic zone extracted and replaced by an implant after a 6–8 week healing period were selected for this study. Hard and soft tissue measurements of the extraction site were obtained pre‐extraction and were repeated 6–8 weeks post‐extraction at defined points using a key. Results After a 6‐ to 8‐week healing period, the total ridge thickness in the crestal midline reduced by 15% of the original value. The buccal plate resorbed in an “inverted V shape”. Forty‐two percentage of subjects had lost 4 mm or more of buccal bone in the midpoint of the extraction socket. Discussion After a 6‐ to 8‐week healing period post‐extraction, there were significant reductions in the hard and soft tissue dimensions of the ridge, most notably on the most coronal mid‐buccal aspect. All implants placed required simultaneous augmentation as a result.